2021
DOI: 10.1111/jan.15115
|View full text |Cite
|
Sign up to set email alerts
|

Self‐care of patients with multiple chronic conditions and their caregivers during the COVID‐19 pandemic: A qualitative descriptive study

Abstract: Aims Explore the self‐care experiences of patients with multiple chronic conditions (MCCs) and caregivers' contributions to patient self‐care during COVID‐19 pandemic. Design A descriptive qualitative design was used. The COREQ checklist was used for study reporting. Methods Individual semi‐structured interviews were used to collect data from patients with MCCs and caregivers selected from the dataset of an ongoing longitudinal study. Data analysis was performed through deductive thematic analysis. The middle‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
(75 reference statements)
1
10
0
Order By: Relevance
“…These included the use of dietary modifications and traditional home remedies such as steam inhalation to prevent COVID-19 and invariably maintain their health. Similar findings were reported by other studies in Italy, 32 United States 33 and Ghana. 34 Although, no study has reported dietary modification and supplementation, 35 or established the effectiveness of steam inhalation 36 could prevent COVID-19, Hibino and Hayashida intimated that in the wake of vaccine hesitancy, effective non-pharmaceutical interventions, healthy lifestyles and improved dietary patterns could improve the health of individuals and reduce the risk for COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…These included the use of dietary modifications and traditional home remedies such as steam inhalation to prevent COVID-19 and invariably maintain their health. Similar findings were reported by other studies in Italy, 32 United States 33 and Ghana. 34 Although, no study has reported dietary modification and supplementation, 35 or established the effectiveness of steam inhalation 36 could prevent COVID-19, Hibino and Hayashida intimated that in the wake of vaccine hesitancy, effective non-pharmaceutical interventions, healthy lifestyles and improved dietary patterns could improve the health of individuals and reduce the risk for COVID-19.…”
Section: Discussionsupporting
confidence: 92%
“…Continuing care takes personalized nursing measures to cultivate their independent ability by strengthening the maintenance of the relationship between medical staff and patients and the integration of medical services [24]. Learn self-care and self-care in daily life, enhance their self-confidence to maximize their physical and mental state, reduce dependence on family members and excessive use of medical resources, and the quality of life will also improve [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…This understanding has increased awareness about the need for self-care among people living with NCDs. Practices of self-care, including adherence to prescribed medications, increasing physical activity, and eating a healthy diet, have varied [ 10 , 24 , 25 ]. While most patients in this study had improved therapeutic and preventive self-care practices, some patients who were experiencing other difficulties in their lives, such as inadequate income, had increased emotional stress and less motivation to use self-care.…”
Section: Discussionmentioning
confidence: 99%